Multi-Stakeholder Innovation in Smart City Discourse: Quadruple Helix Thinking in the Age of “Platforms” - Borghys, Koen; van der Graaf, Shenja; Walravens, Nils; Van Compernolle, Mathias (Frontiers in Sustainable Cities, 2020)
The predominant rhetoric in smart city debates puts the emphasis on collaboration. Conceptualizing, designing, implementing, validating and evaluating solutions to urban challenges with all relevant stakeholders around the table is perceived as the optimal modus operandi in these perspectives. But how does this vision relate to current practices in cities? This paper deals with the observed trend towards more multi-stakeholder collaboration and the resulting complex value networks these stakeholders need to navigate. This is exemplified in what has been called the ‘platformization’ of the urban space by ‘urban service platforms’ (e.g. Uber, AirBnB) as well as in so-called ‘quadruple helix’ approaches to urban innovation. Particularly for (local) government, finding a role in these complex networks has proven challenging. This paper explores the main challenges concerning multi-stakeholder innovation and opportunities related to this topic.